Eco-friendly microencapsulation of Lacticaseibacillus paracasei using Ficus pumila seed extract: A novel plant-based delivery system enhancing probiotic stability and gastrointestinal tolerance - Watcharapong Mitsuwan; Chonticha Romyasamit; Rungruedee Kimseng; Tanakamol Mahawan; Sasi Vimon (Veterinary World)
Background and Aim: Probiotic viability remains a critical challenge during gastrointestinal (GI) transit, storage, and feed processing. Conventional encapsulation materials often fail under acidic and thermal stress. This study aimed to develop and characterize a novel, eco-friendly microencapsulation system using Ficus pumila (FP) seed extract as a natural encapsulating matrix for Lacticaseibacillus paracasei (LP) WU2502, enhancing its functional resilience and storage stability.